Application of the ACMG/NSGC genetic referral guidelines for hereditary renal cell carcinoma at the University of Miami, from 2014 to 2017. Issue 10 (21st June 2021) - Leuchter, Jessica D.; Patel, Priyen M.; Fourzali, Kayla M.; Donenberg, Talia R.; Silva‐Smith, Rachel; Vassallo, Nicolette C.; Blanton, Susan H.; Parekh, Dipen J.; Forghani, Irman
Abstract: Identifying hereditary syndromes among patients with renal cell carcinoma (RCC) is essential for surveillance of affected individuals and their at‐risk family members and for treatment optimization. We conducted a chart review to determine the percentage of patients with RCC who were seen at the University of Miami Health System (UHealth), and met the American College of Medical Genetics (ACMG) and the National Society of Genetic Counselors (NSGC) genetic referral criteria at the University of Miami. Subsequently, we determined the percentage of those who went on to receive genetic evaluation. Patients selected by International Classification of Diseases (ICD) 9/10 codes corresponding to kidney cancer who were at least 18 years of age at the time of diagnosis were included in the study. We included a total of 1443 patients in the final analysis, and after exclusion of charts with incorrect ICD codes, insufficient clinical data, unknown pathology, and patients who were not seen. We used chi‐square analysis, ANOVA, and t ‐test. Of 1443 charts reviewed, 65.7% were male and 34.3% were female. 47.7% self‐identified as White, 39.2% as Hispanic, 9.1% as Black, and 4.0% as "other." The mean age of RCC diagnosis was 60.0 ± 12.4 years old. In total, 47.0% of patients met ACMG/NSGC referral criteria for genetic evaluation. Of those, only 4.2% had documented genetic assessment. This study showed a low adherence to ACMG/NSGC genetic referral guidelines at our institution and a need for increasing patients' and practitioners' awareness about the significance of genetic assessment for RCC patients and their family members.